PTU-129 Anal Evoked Potentials at 'Twitch' Threshold: a New Method for Exploration of Anal Sensory Function. (4th June 2013) - Carrington, E V; Horrocks, E; Connolly, S; Scott, M; Knowles, C
Abstract : Introduction: Faecal incontinence can be associated with impaired anal sensitivity. Anal evoked potentials (EPs) have previously been used to quantify anal sensory function; however the traditional technique of stimulating at a percentage of pain threshold may result in poorly reproducible results with significant inter-individual variability. The aim of this study was to develop a reliable and reproducible method of recording anal EPs, and to define waveform characteristics in healthy volunteers. Methods: Twenty eight healthy volunteers (21 F, median age 34 [range 21–74]) without bowel dysfunction were recruited for the study. Anal EPs were recorded in response to stimulation (using a bipolar electrode) 1cm from the anal verge. In contrast to previous studies, stimulation intensity was delivered at motor threshold (determined by visualisation of an anal 'twitch'). Four sets of 50 stimuli (0.2 Hz frequency, 0.2 ms pulse duration) were given with 5-minute intervals between sets to reduce habituation. A repeat study was performed in 7 volunteers after a minimum interval of 2 weeks. Recordings were taken between channels Cz-A1 and Cz'-Fz (International 10–20 system) in accordance with previously published literature. Runs were averaged and latencies for EP responses were defined, analysed and compared. Results: Motor threshold stimulation (median 20, range 10–36 mA) was well tolerated in all volunteers and resulted in reproducible polyphasic waveforms. The first negative peak (N1) was clearly identifiable on all traces. In the Cz'-Fz channel, the latency to N1 was 130 ± 20 ms (coefficient of variation [COV] = 15%). This was less variable than N1 in Cz-A1 (153 ± 34 ms; COV = 22%) and much less than published previously (COV of N1 = 39%; Remes-Troche et al. Neurogastroenterol Motil 2011). Analysis of repeat studies demonstrated that latencies in channel Cz'-Fz were the most reproducible (ICC of N1 latency = 0.95 [very strong agreement]). Conclusion: Electrical stimulation at motor threshold and recording of evoked potentials from channel Cz'-Fz is a reliable and reproducible method for examination of anal sensory function. Latency to N1 is the most consistent waveform component and is highly reproducible. The technique of stimulation at 'twitch' threshold appears to reduce inter-subject variability and may allow application to further explore both the pathophysiology of anal dysfunction and the effect of treatments aimed at modulating anal neuronal function. Disclosure of Interest: None Declared Reference: Remes-Troche JM, Tantiphlachiva K, Attaluri A, et al . A bi-directional assessment of the human brain-anorectal axis. Neurogastroenterol Motil 2011; 23 : 240–248, e117–248